Wokół problematyki kasacji unii kościelnej w latach 30. XIX wieku w obwodzie białostockim (od unickiego parocha do prawosławnego duchownego) - Matus, Irena (Acta Polono-Ruthenica, 2012)
The process of Union church laicization, after council in Zamoæ, included the clergy, too. The style of liturgy and casual robes was changed. Priestly and deaconly orders were being in Latin style. It was happened that wives and daughters of Union priests were Roman Catholics. There was paid the tithe, but it was not always got to the clergymen. In Bialystok District, that was territory of ethnic and religion borderland, there were laicization as well as process of exerting an Polish influences on uniates. The process of intensive changes in Union church, that caused abolishment of Union and restitution of Orthodox church, was started about the half of the 30-ies XIX century. Those changes included the Uniate clergy all levels. The Latin title of a canon was changed on protojerej title in accordance with the East ritual. The rules of taking holy orders were changed, too. A sys- tem of rewarding the clergy was implemented in accordance with the east hierarchy. Liturgy robes of clergy were changed, too. Wearing surplices was prohibited. Priests were recommended to buy liturgy robes by east rites or to adopted their own chasubles, dalmaticas and copes. It was not interfered to casual wear of the priests. Some of the Uniate priests got married to the Roman Catholic girls. In those cases, marriage was in wifes rites. In 1837 it was prohibited to take holy orders to people, who had got married to the Roman Catholic girls. The Uniate clergy was in a difficult situation. Its basic source of income was churchs lands. In mixed religious environment, it could be improved by tithe paid by pari- shioners to the Roman Catholic priests. In 1828, Senate issued regulation in a case of tithe division between Roman Catholic and Uniate priests. The Uniate priests were changed in the Orthodox in 1839, but that process was being for many years.